2020
DOI: 10.9734/ajahr/2020/v6i430078
|View full text |Cite
|
Sign up to set email alerts
|

Economics of Turmeric Production in Sri Lanka: An Empirical Analysis in Major Turmeric Growing Districts

Abstract: Aims: Turmeric occupies a prominent position among the commercially grown spices in Sri Lanka. However, due to various constraints the performance of turmeric production is not to the expected level. The present study attempts to determine the economics of turmeric cultivation and the problems perceived by the growers related to production and marketing of turmeric. Study Design:  Multistage sampling design. Place and Duration of Study: The study was conducted in the major turmeric growing administ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…The economic and social benefits of turmeric cultivation are significant in Karnataka, impacting both the state economy and the well-being of farmers [17,18]. A decline in turmeric production could harm the state's economy, while an expanding turmeric production system has the potential to boost farmers' incomes, create employment opportunities, alleviate poverty, enhance food security and contribute to overall social development [19,[20][21][22]. Recognizing the potential for establishing a self-sufficient commercial venture in turmeric cultivation, there is a timely and statewide need for information on the economics of turmeric production.…”
Section: Introductionmentioning
confidence: 99%
“…The economic and social benefits of turmeric cultivation are significant in Karnataka, impacting both the state economy and the well-being of farmers [17,18]. A decline in turmeric production could harm the state's economy, while an expanding turmeric production system has the potential to boost farmers' incomes, create employment opportunities, alleviate poverty, enhance food security and contribute to overall social development [19,[20][21][22]. Recognizing the potential for establishing a self-sufficient commercial venture in turmeric cultivation, there is a timely and statewide need for information on the economics of turmeric production.…”
Section: Introductionmentioning
confidence: 99%
“…This clearly indicates the necessity of various improved agro technical practices adoption to increase the productivity. Abeynayaka et al [9] reported that lack of knowledge on agricultural practices and non availability of labour as key reasons which affect turmeric productivity. Dipika [10] has studied the technological gap in turmeric production.…”
Section: Introductionmentioning
confidence: 99%
“…Mainly it is used as a condiment and coloring agent in the food industry. Additionally, it has a great demand in many industries such as the cosmetic, pharmaceutical industry, and ayurvedic medicines (Abeynayaka et al, 2020). Further, it is used to prepare curry mixtures, color in textiles, and prepare specific paints.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, turmeric production in Sri Lanka is not self-sufficient. To keep pace with the increased demand, a significant proportion of the local demand is being imported, putting a heavy burden on national income (Abeynayaka et al, 2020).…”
Section: Introductionmentioning
confidence: 99%